2015
DOI: 10.1002/ajmg.c.31425
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of mucocutaneous manifestations in 277 patients with joint hypermobility syndrome/Ehlers‐Danlos syndrome, hypermobility type

Abstract: Cutaneous manifestations are a diagnostic criterion of Ehlers-Danlos syndrome, hypermobility type (EDS-HT) and joint hypermobility syndrome (JHS). These two conditions, originally considered different disorders, are now accepted as clinically indistinguishable and often segregate as a single-familial trait. EDS-HT and JHS are still exclusion diagnoses not supported by any specific laboratory test. Accuracy of clinical diagnosis is, therefore, crucial for appropriate patients' classification and management, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 27 publications
1
38
0
1
Order By: Relevance
“…The Ehlers–Danlos syndromes (EDS) comprise a heterogeneous group of conditions of connective tissue with a broad spectrum of involvement including the musculoskeletal, cardiac, dermatologic, ophthalmologic, gastrointestinal, autonomic, and neurodevelopmental systems (Malfait et al, ). While joint hypermobility is common in the pediatric population (10–15% prevalence) (Cattalani et al, ), the prevalence of most forms of EDS meeting diagnostic criteria in children ranges from 4.6 to 13% (Tobias et al, ; Sperotto et al, ), with the hypermobile type being most common. It has been suggested that joint hypermobility syndrome and hypermobility EDS represent a spectrum of the same disorder (Tinkle et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The Ehlers–Danlos syndromes (EDS) comprise a heterogeneous group of conditions of connective tissue with a broad spectrum of involvement including the musculoskeletal, cardiac, dermatologic, ophthalmologic, gastrointestinal, autonomic, and neurodevelopmental systems (Malfait et al, ). While joint hypermobility is common in the pediatric population (10–15% prevalence) (Cattalani et al, ), the prevalence of most forms of EDS meeting diagnostic criteria in children ranges from 4.6 to 13% (Tobias et al, ; Sperotto et al, ), with the hypermobile type being most common. It has been suggested that joint hypermobility syndrome and hypermobility EDS represent a spectrum of the same disorder (Tinkle et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The original sets of criteria raised from an “opinion”‐based approach from the converging experience of a few experts. Conversely, in the last years, many papers refine some of the previously identified pleiotropic features of the syndrome, such as the mucocutaneous and ocular involvement [Gharbiya et al, ; Castori et al, ], and underline other entirely novel manifestations, such as gastrointestinal involvement and autonomic dysfunction [Zarate et al, ; De Wandele et al, ]. The role of fatigue and chronic pain is also emphasized in JHS/EDS–HT [Voermans et al, ,; Voermans and Knoop, ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of fatigue and chronic pain is also emphasized in JHS/EDS–HT [Voermans et al, ,; Voermans and Knoop, ]. While many articles offer a global impact of these features in JHS/EDS–HT, the observation of families and heterogeneous patients’ cohorts suggest an age‐influenced phenotype [Castori et al, , , , , ]. Nevertheless, though originally considered relevant features, little attention was put on the extent and evolution of anthropometry, consequences of joint instability and orthopedic traits in JHS/EDS–HT.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][9][10][11] Various elements contribute to this area of uncertainty. However, intra-and interfamilial variability tells a much wider clinical presentation and significant overlap with other EDS types and heritable soft connective tissue disorders (HSCTDs).…”
mentioning
confidence: 99%
“…However, intra-and interfamilial variability tells a much wider clinical presentation and significant overlap with other EDS types and heritable soft connective tissue disorders (HSCTDs). [2][3][4][5][9][10][11] Various elements contribute to this area of uncertainty. JHM seems to naturally decrease with age 5 as more widely demonstrated in hEDS.…”
mentioning
confidence: 99%